Simple computer model for the quantum Zeno effect - Wallace, D (2001)
This paper presents a simple model for repeated measurement of a quantum system: the evolution of a free particle, simulated by discretizing the particle's position. This model is easily simulated by computer and provides a useful arena to investigate the effects of measurement upon dynamics, in particular the slowing of evolution due to measurement (the quantum Zeno effect). The results of this simulation are discussed for two rather different sorts of measurement process, both of which are (simplified forms of) measurements used in previous simulations of position measurement. A number of interesting results due to measurement are found, and the investigation casts some light on previous disagreements about the presence or absence of the Zeno effect. ©2001 The American Physical Society.